Comparing the Global Tariff and Actual Costs of Surgeries at Imam Khomeini Hospital Affiliated with Kermanshah University of Medical Sciences - Jamil Sadeghifar; Nasim Eyvani; GHasem Rajabi Vasukolai; Naser Farhamand Moghadam; Shahram Ekhtyari (بیمارستان)
Background and purpose: Creating sustainable income, enhancing economic perspectives, optimizing and managing costs, and generating revenue in the health system—especially in hospitals, which are primary providers of medical services—are critically important. These have become priority, vital policies. This study was conducted to compare the recorded costs in patient files with the approved global tariffs for surgeries at Imam Khomeini Hospital in Kermanshah. Methods: This descriptive cross-sectional study was conducted at Imam Khomeini Educational and Therapeutic Hospital in Kermanshah in 2022. The research population included financial records for surgeries under the global tariff, covering the last six months of 2020 and the first six months of 2021. Data were collected from the Hospital Information System (HIS) and analyzed using SPSS-22 software. Results: Among 357 cases involving 13 types of surgeries reviewed in this study, tonsillectomy, pterygium, and appendectomy surgeries resulted in losses, while other surgeries were profitable. Considering the average actual cost of each surgery, in 14% of the surgeries, the global tariff was lower than the average actual cost, while in 86% of cases, the global tariff proved beneficial to the hospital. Conclusion: Although most centers that apply the global surgery tariff are financially unprofitable, implementing operational plans based on essential resources and designing corrective actions to reduce global costs—particularly by managing patient length of stay—can improve efficiency and productivity.